(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Public charging networks for Electrical Vehicles (EV) is on the rise, with more than 1 million EV deployed worldwide. Whether for economic benefits (higher price per KWh for a faster charging) or for the sole purpose of priority, it has become a point of interest to set a strategy on how to prioritize EVs charging from a single network, especially if the power source is limited as in the case of renewable energy. In this paper a strategy will be proposed for EV charging station to give priority to certain EV to charge faster and prevent the SOC from being the main drive in case of limited power source. The aim of this paper is to design and evaluate a charging algorithm that will prioritize EV and fill some faster than others. This approach can be utilized by private businesses to categorize and lower the fees for charging, making EVs more attractive economically. The scenario considered for this paper is an office building parking lot that is shaded by solar photovoltaic (PV) panels. This paper discussed Time-multiplexing method, a strategy to charge EV from solar energy.